PENGARUH BUDAYA SEKOLA TERHADAP KUALIATAS PEMBELAJARAN DI SMA NEGERI 1 KRIAN - Sefia Rahmawati; Dea Miranda, Shabrina Poppy Darmatian, Felda Ramadhanti, Alven Risqi Muchlasin, Ayu Wulandari (CV. ADIBA ASIHA AMIRA, 2024)
This study looks at how school culture affects the standard of instruction at SMA Negeri 1 Krian in Sidoarjo Regency. The distinctive qualities and personality of a school that influence the learning environment, student motivation, and involvement are referred to as its school culture. The relationship between learning quality and school culture was examined using a quantitative methodology. School culture has a significant influence on the learning process, based on the ANOVA test which produced a significance value of 0.000 < (0.05). A student's character is shaped and their educational experience is enhanced by factors including school rules, extracurricular activities, and acknowledging student accomplishments. This study emphasizes how crucial it is to develop a positive school culture in order to provide a helpful and productive learning environment, which will ultimately raise the standard of instruction and improve student results